(NsTATISTI^ESKAQ OPTIKA (B:s (NpER(B. (NS ANGL(B. /s - (NgUDMEN(B, (NdVOZEF u(B.s; (NkOKIN(B, (Na(B.(Na(B.s; (NsKROCKIJ(B, (Ng(B.(Nw(B.s ((NmOSKWA (B:s (NmIR(B,s, 1988)
(NbIBLIOGR(B. (NW KONCE GLAWs
(NpREDM(B. (NUKAZ(B.: (NS(B. 512-521s
Keywords: (NoPTIKAs